2022
DOI: 10.3389/fneur.2022.880907
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Calf Circumference Measurement, SARC-F Questionnaire, and Ishii's Score for Screening Stroke-Related Sarcopenia

Abstract: ObjectiveThe purpose of this study was to investigate the accuracy of sarcopenia diagnosis in patients with stroke using calf circumference (CC), SARC-F questionnaire, and Ishii's score in comparison with the Asian Working Group for Sarcopenia 2019 (AWGS) sarcopenia diagnostic criteria.Materials and MethodsIn this cross-sectional study, a total of 364 consecutive patients with stroke were enrolled and evaluated with the CC measurement, SARC-F questionnaire, and Ishii's score. The diagnostic accuracy was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…44,45) Additionally, the presence of cognitive decline might have influenced the accuracy of the results as the SARC-F is a self-report questionnaire; thus, it depends on a participant's ability to accurately estimate their physical abilities. 46) In contrast, Yao et al 47) showed that when validated against the 2019 AWGS diagnostic criteria among patients with stroke in China, the sensitivity and specificity of the sarcopenia screening tools were as follows: SARC-F (sensitivity of 94.7%; specificity of 40.0%), Ishii's score (sensitivity of 90.1%; specificity of 36.0%), and CC alone (sensitivity of 81.8%; specificity of 90.1%). Ishii's score was derived from a sex-specific formula that included age, HGS, and CC values.…”
Section: Discussionmentioning
confidence: 94%
“…44,45) Additionally, the presence of cognitive decline might have influenced the accuracy of the results as the SARC-F is a self-report questionnaire; thus, it depends on a participant's ability to accurately estimate their physical abilities. 46) In contrast, Yao et al 47) showed that when validated against the 2019 AWGS diagnostic criteria among patients with stroke in China, the sensitivity and specificity of the sarcopenia screening tools were as follows: SARC-F (sensitivity of 94.7%; specificity of 40.0%), Ishii's score (sensitivity of 90.1%; specificity of 36.0%), and CC alone (sensitivity of 81.8%; specificity of 90.1%). Ishii's score was derived from a sex-specific formula that included age, HGS, and CC values.…”
Section: Discussionmentioning
confidence: 94%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/nu15010113/s1, Table S1: Search strategy for the systematic review; Table S2: Summary of the included studies [53][54][55][56][57][58][59][60][61].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Search strategy for the systematic review; Table S2: Summary of the included studies [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
mentioning
confidence: 99%
“…We investigated sarcopenia risk using the Screening for Sarcopenia questionnaire (SARC-F) [30], which allows rapid screening using self-reported data on falls, stair climbing, rising from a chair, walking with assistance, and strength. SARC-F was recommended by the AWGS 2019 as a tool with excellent specificity to screen sarcopenia in communitydwelling older adults [31]. In addition, its reliability and validity have been proven in several studies [32,33].…”
Section: Sarcopenia Riskmentioning
confidence: 99%